The role of the individual in the development of innovation from the perspective of organizational operation - Véghné Kohut, Dorottya (Acta Carolus Robertus, 2022)
Innovation means in the 21st century only possible way for businesses to operate is to stay competitive in the market. Applying innovation provides an opportunity to adapt to a changing environment. Competitiveness is important not only for companies but also for nations because it is the foundation for social prosperity and continued economic growth. However, the creation of economic conditions, regulatory, infrastructural and technological factors is not enough for this, but the social individuals present in the economy also contribute greatly to this process with their thoughts and decisions. Management and corporate operations are significantly influenced by the motivation, human values, time perspectives and personality typology of employees and managers. These elements are not negligible test factors in organizational performance.
Keywords: creativity; innovation; time perspective; organizational operating; competitiveness